(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Provides the style of benchmarking the best possible use whenevaluating the performance and evaluation, as well as improved performance,due to its consistency with the principles of good evaluation of theperformance, an extension of the completion of several functions of the timeand cost less, thereby increasing the efficiency of the management of theinstitutions, especially institutions, the media, as it became public the future ofthe message sender to the same time Zaorosaúl new media is challenging thetraditional media of what distinguishes this new interactive media and mass ledto this transition . However, the media Aljdidhoosaúl traditional mediacontinue to coexist and reinforce each Menhmaalakhr, for his wealth offreedom of opinion media among the public the future of the message and thesender has reached the interactive mass is enhanced thanks to the new media byusing the means of non-conventional. Research has come to a set ofconclusions, the most important that when assessing and evaluating performedusing the tool effective and appropriate tool like Almgarnaa to Marjaahllaalamis the new media complement to traditional media and enhanced its strengthsMtlavia weaknesses, because he focuses on the satisfaction of the public (theconsumer (by strengthening the role of the receiver of the message sender hasthis Majolh (new media), a benchmark for the performance of the media ininstitutions media and make it a standard of conduct administrative sensewithin the organizational structure, embodying the administrative contactthrough cognition of the importance of the media, especially interactive mass..